Quality of Life Allergic Rhinitis after Probiotic Combination Supplementation - Wardani, Andriana Tjitria Widi; Soetoko, Anita Soraya (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Probiotics are potential as a therapy for allergy sufferers, which can increase the ratio IFNÃƒÂ£, IL4. However, the effects of probiotics on the quality of life of patients with allergic rhinitis have not been developed yet. This study aimed to determine the effect of a combination of probiotics on the quality of life of patients with allergic rhinitis.Design and Methods: This study used a randomized design with post test control group design. The populations in this study were men and women aged 18-25 years who suffer from allergic rhinitis with moderate to severe according to the WHO criteria. This study uses two groups: the group treated by administration of a combination of probiotics and the control group were given a placebo. Quality of life was assessed by checklist scores and levels of IgE. Data were analyzed using the Mann Whitney U test with 95% confidence intervals.Results: The results of statistical analysis showed no significant difference between the quality of life of allergic rhinitis sufferers control and treatment groups (p> 0.05). However, there are significant differences between the mean levels of IgE allergy sufferers rhintis control and treatment groups (p <0.05).Conclusion: Probiotic treatment did not affect the quality of life of patients with allergic hinitis but a reduction in the levels of IgE (Sains Medika, 4(2):157-164).